A WONDERFUL JOURNEY INTO THE FICTIONAL WOODS OF REGENCY AND VICTORIAN PERIOD: FROM LIZZIE BENNET TO JANE EYRE - Moreira, Luciane de Oliveira (Organon, 2018)
This text invites the reader to a journey into the fictional woods of two important authors of English literature: Jane Austen and Charlotte Brontë. Through a close reading of Lizzie Bennet and Jane Eyre, this work unfolds the story of two fascinating characters. The first one is from Jane Austen’s most famous novel Pride and Prejudice, the second one is from Charlotte Brontë’s masterpiece Jane Eyre. Their social context is not distant, although Brontë had once declared she was not a fun of Austen’s stories, I dare to say that Lizzie opens the way to Jane follows. In this sense, this article put these characters side by side in order to show their similarities, differences and evolution as women in the English society of the 19th century. The intention is to search in art and literature some symbolic ways of dealing with some aspects of real life such as womanhood. KEYWORDS: Jane Austen; Charlotte Brontë; English literature; Female Characters.